2013
DOI: 10.1038/onc.2013.129
|View full text |Cite
|
Sign up to set email alerts
|

Proof-of-concept rare cancers in drug development: the case for rhabdomyosarcoma

Abstract: Rare diseases typically affect fewer than 200,000 patients annually, yet because thousands of rare diseases exist, the cumulative impact is millions of patients worldwide. Every form of childhood cancer qualifies as a rare disease-including the childhood muscle cancer, rhabdomyosarcoma (RMS). The next few years promise to be an exceptionally good era of opportunity for public-private collaboration for rare and childhood cancers. Not only do certain governmental regulation advantages exist, but these advantages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 200 publications
2
34
0
Order By: Relevance
“…The human MB1208-1 human skeletal myoblast cell line was kindly provided by Dr. Louis Kunkel (Boston Children’s Hospital, Massachusetts). Characteristics of these human RMS (Hinson et al, 2013; Sokolowski et al, 2014) and skeletal myoblast (Alexander et al, 2011) cell lines have been reported previously.…”
Section: Methodsmentioning
confidence: 83%
“…The human MB1208-1 human skeletal myoblast cell line was kindly provided by Dr. Louis Kunkel (Boston Children’s Hospital, Massachusetts). Characteristics of these human RMS (Hinson et al, 2013; Sokolowski et al, 2014) and skeletal myoblast (Alexander et al, 2011) cell lines have been reported previously.…”
Section: Methodsmentioning
confidence: 83%
“…A battery of human RMS cell lines are available for probing — a collection that has been expertly reviewed 20,26 . Here, we focus instead on genetically modified RMS model cells.…”
Section: Genetically Modified Rms Cellsmentioning
confidence: 99%
“…Despite these advances, therapies targeting molecular RMS oncogenic drivers are lacking. (For excellent reviews in these areas, we refer readers to Sokolowski et al 20 , Hettmer et al 21 ; and Keller and Guttridge 22 .) Consequently, investigators have made substantial efforts over the past decade to generate new genetic tools with which to dissect RMS (fig.…”
mentioning
confidence: 99%
“…Families affected by this cancer, patient advocates, clinicians, and scientists need to coalesce their efforts to garner sufficient support from funding sources and the pharmaceutical industry to support the development of curative therapies. Existing preliminary data, strategic considerations by relevant pediatric collaborative groups, and a deep clinical need may provide a fertile ground for partnerships between academic groups and industry (Sokolowski et al 2014). …”
Section: Strategic Considerationsmentioning
confidence: 99%
“…Insufficient access to fresh RMS tissue has hindered progress in RMS research. Moreover, there are few existing human RMS cell lines, and these lines are not widely distributed (Sokolowski et al 2014). Tumor biology initiatives are needed to collect sufficient amounts of fresh tumor material from patients with RMS (both children and adults) to support tumor profiling efforts and the generation, long-term storage, and distribution of new cell lines and xenografts for experimentation.…”
Section: Strategic Considerationsmentioning
confidence: 99%